The importance of networks in the transnational mobility of higher education students: attraction and satisfaction of foreign mobility students at a public university. Issue 9 (1st September 2016) - Pedro, Eugénia; Franco, Mário
Abstract : Advancing the understanding of academic mobility becomes essential since this phenomenon is gaining prominence in the context of the internationalization of European higher education, with repercussions in economic terms for the host institution itself and its surrounding region. From a network theory perspective, this study intends to understand what motivates students in transnational mobility (TM) to seek certain Institutions of Higher Education rather than others. In keeping with the state-of-the-art, the aim is also to obtain indications that associate, or not, those students' previous contact with social networks. Through research of a quantitative, exploratory nature, this study presents results referring to 81 TM students at a Portuguese state university, University of Beira Interior. From these results, it can be inferred that the public and private reasons that attract and perpetuate the TM of higher education students are associated with the adoption of social networks. Some implications for theory and practice are also presented.